Residual effect of methomyl and chlorpyrifos pesticides on tomato fruits produced in Banias region - ابراهيم, فاتن; ديمة الدياب, (Latakia University Journal -Medical Sciences Series, 2023)
Food contamination with agricultural pesticides is considered one of the important topics at the present time, as a result of the harmful effects of these pesticides on human health in the long term. Tomatoes were chosen as one of the important vegetables widely consumed for their health benefits and are largely produced in the coastal region. The presence of both methomyl and chlorpyrifos was detected and the concentrations of these pesticides were determined using a gas chromatography device equipped with a flame ionization detector (FID). The results showed that about 70% of the samples contained pesticides, as chlorpyrifos was found in 27 samples in a range of concentrations ranging from 0.019-988 mg / kg, and all samples exceeded the MRL value approved by the European Union, of 0.01 mg / kg, and methomyl was found in 13 samples in the range The concentrations ranged between 0.028 – 188.6 mg/kg, and all samples exceeded the MRL value approved by the European Union of 0.01 mg/kg, noting that methomyl is currently a pesticide that is banned from use globally.